The impact of climate risks on green technology innovation: an empirical study based on panel data of 269 cities in China - Yangyulong Wu (Frontiers in Environmental Science)
Climate risks include two elements: physical risks and transition risks. Exploring the impact of climate risks on green technology innovation contributes to sustainable development. This study uses panel data from 269 cities in China from 2008 to 2022 to explore the impact of climate risks on green technology innovation, and it employs Spatial Dubin Models for spatial effects analysis. The main research conclusions are as follows. First, the two components of climate risks—physical risks and transition risks—significantly hinder green technology innovation. Second, physical risks suppress green technology innovation by reducing market potential, while transition risks do so by decreasing foreign direct investment. Third, over time, green technology innovation shows a spatial clustering pattern of “low-low” and “high-high.” Fourth, physical risks create negative spatial spillover effects, while transition risks generate positive ones. Fifth, the spatial spillover effects of physical risks are mainly seen in the central region, while those of transition risks are primarily observed in the eastern and western regions, indicating significant regional heterogeneity. Finally, transition risks promoted green technology innovation in the period of 2018–2022, which is different from their suppressive effects in other time periods. In general, this study establishes a more comprehensive analytical framework that fills existing research gaps.